Bio-inventory of terrestrial gastropod species in Northern Mindanao, Philippines - VERONICA B. TAÑAN; NANETTE HOPE N. SUMAYA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Tañan VB, Sumaya NHN. 2024. Bio-inventory of terrestrial gastropod species in Northern Mindanao, Philippines. Biodiversitas 25: 3391-3402. Gastropods are the largest class in the phylum Mollusca, with an estimated 70,000 to 76,000 species. The prevalence of gastropods is undeniable evidence of their successful adaptation to various habitats, including terrestrial, freshwater, and marine environments. Slugs and snails are extremely effective in the terrestrial environment, where they are involved with several ecological activities such as nutrient recycling, decomposing waste material, and calcium enrichment in calcium-deficient habitats. However, many species (notably the non-indigenous ones) are well-known pests that damage crops, increase pesticide demand, harm natural ecosystems, reduce native biodiversity, and even carry pathogens and parasites. Northern Mindanao is one of the regions in Mindanao, Philippines, with abundant agricultural resources. In comparison to other taxa in Mindanao, gastropod species have received less attention from researchers. Thus, we collected, characterized, and delineated species of gastropods from the different agricultural areas in Northern Mindanao, Philippines. During sampling, environmental parameters were recorded, and it was established which gastropod species are associated with crops and, at their worst, can become pests to banana (Musa acuminata Colla), corn (Zea mays L.), cabbage (Brassica oleracea L.), carrots (Daucus carota L.), rice (Oryza sativa L.), eggplant (Solanum melongena L.), chayote (Sechium edule (Jacq.) Sw.), radish (Raphanus sativus L.), and many more. Morphology and morphometrics following published protocols on the collected organisms successfully characterized the gastropod species. Slug species, namely, Laevicaulis alte (Férussac, 1822), Sarasinula plebeia (P.Fischer, 1868), and Deroceras (Deroceras) laeve (O.F.Müller, 1774) and snail species, Lissachatina fulica (Férussac, 1821), Pomacea canaliculata (Lamarck, 1822), Subulina octona (Bruguière, 1789), Oxychilus (Ortizius) alliarius (J.S.Miller, 1822), and Bradybaena similaris (A.Férussac, 1822), were identified. The study reveals that exotic terrestrial gastropods are prevalent in the agricultural areas across Northern Mindanao. Consequently, additional surveys are necessary to determine the extent of their dispersal, crop preferences, pest status, and to its associated parasites within the Philippines.